If F ( i ) = i 1 , then calculate the whole part of:
i = 1 ∑ 1 , 0 0 0 , 0 0 0 F ( i )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Comparing the area under the curve for the decreasing function x 1 , we have for any positive integral N 1 + ∫ 1 N x 1 d x > i = 1 ∑ N N 1 > ∫ 1 N + 1 x d x This implies, 2 N − 1 > i = 1 ∑ N N 1 > 2 N + 1 − 2 Putting N = 1 0 6 , we get 1 9 9 9 > i = 1 ∑ N N 1 > 1 9 9 8 This gives us the desired result.
Sir, How did you get the first conclusion ??
Problem Loading...
Note Loading...
Set Loading...
First of all, let’s find an upper and lower bound for F(i)
1. Lower bound for F(i):
It can easily be shown that: 2 ( i + 1 − i ) < F ( i )
Proof:
( i + 1 − i ) = i + 1 + i ( i + 1 − i ) X ( i + 1 + i ) =
i + 1 + i 1 < i + i 1 = 2 i 1
Therefore :
2 ( i + 1 − i ) < F ( i ) . . . ( 1 )
2. Upper bound for F(i):
Also, It can easily be shown that: F(i) < 2 ( i − i − 1 )
Proof:
( i − i − 1 ) = ( i + i − 1 ) ( i − i − 1 ) X ( i + i − 1 ) =
( i + i − 1 1 > ( i + i 1 ) ) = 2 i 1
Therefore :
2 ( i − i − 1 ) > F ( i ) . . . ( 2 )
Now we have: ∑ i = 1 1 , 0 0 0 , 0 0 0 F ( i ) = 1 + 0 . 0 0 1 + ∑ i = 2 9 9 9 , 9 9 9 F ( i ) = 1.001 + S1 ... (3) )
W h e r e S 1 = ∑ i = 2 9 9 9 , 9 9 9 F ( i )
In order to calculate this total, let’s find the sum of lower and upper bound of it.
Value of lower bound sum = ∑ i = 2 9 9 9 , 9 9 9 2 ( i + 1 − i ) = 2 [ ( 3 − 2 ) + ( 4 − 3 ) + … ( 1 0 0 0 0 0 0 − 9 9 9 9 9 9 ) ] = 2 [ ( 1 0 0 0 0 0 0 − 2 ) ] = 2 [ 1 0 0 0 − 1 . 4 1 4 ] = 2 [ 9 9 8 . 5 8 6 ] = 1 9 9 7 . 1 7 2
Value of upper bound sum = ∑ i = 2 9 9 9 , 9 9 9 2 ( i − i − 1 ) = 2 [ ( 2 − 1 ) + ( 3 − 2 ) + … ( 9 9 9 9 9 9 − 9 9 9 9 9 8 ) ] = 2 [ 9 9 9 9 9 9 − 1 ] = 2 [ 9 9 9 . 9 9 9 − 1 ] = 2 [ 9 9 8 . 9 9 9 ] = 1 9 9 7 . 9 9 8
From (1), (2) and (3) we have:
1 . 0 0 1 + 1 9 9 7 . 1 7 2 < ∑ i = 1 1 , 0 0 0 , 0 0 0 F ( i ) < 1 . 0 0 1 + 1 9 9 7 . 9 9 8
1 9 9 8 . 1 7 3 < ∑ i = 1 1 , 0 0 0 , 0 0 0 F ( i ) < 1 9 9 8 . 9 9 9
Therefore, the whole part of: ∑ i = 1 1 , 0 0 0 , 0 0 0 F ( i ) = 1 9 9 8
Answer = 1 9 9 8